NINETIES ADVANCEMENT IN THE CROP MECHANIZATION AND OF THE SOCIAL EXCLUSION IN THE SUGAR CANE PRODUCTION IN THE STATE OF SÃO PAULO - Gonçalves, José Sidnei (Science & Technology Journals, 1999)
The technological changes of sugar cane production, in the State of São Paulo, Brazil, had its speed accelerated with the expansion of mechanized harvest as an environmental friendly legislature that prohibited the straw burning. In this context, the paper builds various scenarios on which there would be a different impact in the cultivated area and variation in labour force demand of main São Paulo farming activity. It concludes that, remaining the currents conditions, the perspective of these two parameters in all possible settings is to attain higher social exclusion levels, as they mean changing from a precarious employment situation to one with large unemployment of a large number of workers.